Energy use efficiency in mechanized cultivation of castor (Ricinus communis L.): Energy use efficiency in mechanized cultivation of castor (Ricinus communis L.) - P KATHIRVELAN,; S R VENKATACHALAM,; P ARUTCHENTHIL,; M DEIVAMANI, (Journal of Oilseeds Research, 2020)
The highest seed yield (1765 kg/ha) was recorded under normal practices than mechanized practices (1640 kg/ha). A total of 63 man days/ha were employed with a time consumption of 442 hr/ha against normal practices (153 man days/ha with 1244 hr/ha). Thus, higher gross return of ` 67,240/ha, return above variable cost of ` 46,740/ha with a benefit cost ratio of 3.28 was realized under mechanized cultivation.